Family and economic growth in Poland. New estimation results - Sztaudynger, Jan Jacek (Annales. Etyka w Życiu Gospodarczym, 2019)
Economic growth is mostly explained by investments and employment growth. Since the mid-1990s various social categories have been introduced into the economic growth analysis, such as trust, crime and income inequality, etc. According to sociology and psychology, it is the family that constitutes interpersonal relationships and is an indicator of happiness and quality of life. It can be said that happy people better fulfil their social roles and also work better. We put forward the hypothesis that family ties have an influence on economic growth. More precisely: the more divorces (relative to existing marriages) there are, the slower economic growth is. This hypothesis was confirmed in an analysis of Poland’s economy in the years 1995–2017. Due to the disintegration of family ties measured by the divorce rate, Poland’s annual economic growth was slowed by about a 1 percentage point on average. This estimation is based on the productivity (GDP to labor ratio) growth model which, along with the divorce rate, also includes the investment and new marriage rates.